Low RKIP expression associates with poor prognosis in bladder cancer patients - Afonso, Julieta Alexandra Pereira (2013)
Urothelial bladder cancer (UBC) is a heterogeneous type of disease. It is urgent to screen biomarkers of tumour aggressiveness in order to clarify the clinical behaviour and to personalize therapy in UBC patients. Raf kinase inhibitory protein (RKIP) is a metastasis suppressor, and its downregulation is associated with metastatic events in an increasing number of solid tumours. We evaluated the clinical and prognostic significance of RKIP expression in patients with high risk of progression UBC. Using immunohistochemistry, we determined RKIP expression levels in a series of 81 patients with high-grade pT1/pTis or muscle-invasive UBC. Staining of CD31 and D2-40 was used to assess blood and lymphatic vessels, in order to distinguish between blood and lymphatic vessel invasion (LVI). We found that 90 % of pT1/pTis tumours, 94 % of non-muscle invasive papillary tumours and 76 % of the cases without LVI occurrence expressed RKIP in > 10 % of cells. In this group, we observed a subgroup of tumours (42 %) in which the tumour centre was significantly more intensely stained than the invasion front. This heterogeneous pattern was observed in 63 % of the cases with LVI. Low RKIP expression was associated with poorer 5-year disease-free and overall survival rates, and remained as an independent prognostic factor for disease-free survival. Loss of RKIP expression may be an important prognostic factor for patients with high risk of progression bladder cancer.